Proceedings of the 13th World Conference on Titanium 2016
DOI: 10.1002/9781119296126.ch172
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening Strategy for A Ductile Metastable B Titanium Alloy Using Low Temperature Aging

Abstract: Low temperature aging treatments, at around isothermal transition temperature (T iso ), were performed on a ductile metastable Ti-12Mo alloy displaying a combination of TRIP (Transformation induced Plasticity) and TWIP (Twinning induced Plasticity) effects. The main objective is to improve the yield strength of the material while keeping the advantage of combined stress induced phase transformation and mechanical twinning, as observed in the solution treated samples. Based on a resistometric investigation dedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Sun et al [11] reported that at low aging temperature (150 °C for 60 s,) the yield strength of the titanium alloys increased to 730 MPa from 480 MPa. The aging temperature above 200 °C, the alloy has a detrimental effect on the ductility.…”
Section: Introductionmentioning
confidence: 99%
“…Sun et al [11] reported that at low aging temperature (150 °C for 60 s,) the yield strength of the titanium alloys increased to 730 MPa from 480 MPa. The aging temperature above 200 °C, the alloy has a detrimental effect on the ductility.…”
Section: Introductionmentioning
confidence: 99%